Millieu Therapy Metode Kreasi Seni Modifikasi Lingkungan Terhadap Tingkat Harga Diri Remaja - Athi Linda Yani; Arifa Retnowuni (Puslitbang Sinergis Asa Professional, 2020)
Adolescence is a transition period between childhood and adulthood. Massive changes from childhood to adulthood are common at ages 13 to 20 years. Previous research discusses the difficulties of social interaction with peers, social relationships with groups, and difficulty communicating with a social new environment. Some students expressed stress with the number of Islamic boarding school rules, controlled and far from parents. At the same time, 32% of people agreed that they were not confident, sad, anxious, afraid of intimidation, and decreased learning enthusiasm. People who looked down on trust would have an external and internal impact. The external consequence is difficulty reaching academic achievement and social relations. The internal consequence is difficulty reaching internal self-concept, unclear, complicated, uncertain self goals, and pessimistic in the future challenge. This study aimed to know the level of self-esteem of students after being given milieu therapy with environmental modification art creation. The study design uses pre-experimental with pre-post test design of one group. The sampling technique was purposive sampling. Samples were taken as many as 24 respondents and divided into 4 groups of 6 people in each group. The intervention was given for 3 weeks. In this study, measuring instruments used a questionnaire using Rosenberg and data analysis using the Wilcoxon test signed a ranking test. The statistical analysis showed the results of p = 0.030 <α. There was a milieu effect of therapeutic methods of environmental modification art creation on students' level of self-esteem living in the dormitory. Milieu therapy can increase awareness and self-confidence between peers with the approval of self-confidence and commitments agreed between friends.